Accreditation of Viet Nam's higher education: Achievements and challenges after a dozen years of development. Issue 4 (4th September 2017) - Nguyen, Huu Cuong; Evers, Colin; Marshall, Stephen
Abstract : Purpose: The purpose of this paper is to investigate the development of Viet Nam's approach to higher education quality assurance during the past dozen years since its establishment, focusing on the achievements and challenges. Design/methodology/approach: This is a desktop analysis study. The paper analyses the policies and practices related to the development of Viet Nam's higher education accreditation system by reviewing associated literature. Findings: The research has found out that there are several achievements, including: the development of the accreditation framework; establishment of accrediting agencies; completion of almost universities' self-assessment reports; implementation of external assessment exercise at some institutions, a few of which were awarded accreditation certificates. However, there remain a number of challenges related to the independence of the accrediting agencies, human resources, accreditation standards and criteria, institutions' awareness about accreditation and the pace of accreditation implementation. Research limitations/implications: The primary limitation of this study is the research methodology which merely relies on document analysis. It would be more credible if the findings could be triangulated with data taken from other sources such as interviews with key stakeholders. Originality/value: On the basis of the analysis of achievements and challenges at both macro and micro levels, discussion and recommendations are made for future policy-making and management in the field of higher education accreditation.